Analisis Pola Kalimat Teks Berita pada Media Surat Kabar Kompas Edisi Februari 2024 sebagai Sumber Bacaan Siswa SMA - Anugrah Bintang; Rika Ardiana Yuni Cahyaningrum; Neri Vedita Putri; Nafikha Putri Arthamevia Maharani; Riri Citra Melisa; Asep Purwo Yudi Utomo; Sugiana Sugiana (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
In today's world, technology has revolutionized the process of information discovery, making it faster and more efficient. Technological advancements have had a significant impact on how information is collected. Previously, information was sourced from newspapers and other outlets but lacked direct conveyance. The emergence of the Internet made information readily accessible, allowing for the rapid reporting and dissemination of events on a national and global scale. This easy access to information enables people to stay abreast of global events. The goal of news text analysis is to offer information and insights to the public about recent events, as news plays an integral role in human life. This research method employs a qualitative descriptive approach to generate written data, typically in a narrative format. The findings identified six distinct patterns: : 3 S-P-K-K, 2 S-P-O-Pel, 3 S-P, 2 S-P-O, 1 S-P-O-K, dan 3 S-P-K. This research can serve as a valuable educational tool for high school students.